Relação entre a implementação do sistema Universidade Aberta do Brasil (UAB) e a migração interna por motivo de estudos nas cidades-polo de apoio presencial em Minas Gerais - Adálcio Carvalho de Araújo (2022)
This paper analyses the relationships between the implementation of distance learning courses from the Universidade Aberta do Brasil (UAB) program in municipalities located in the state of Minas Gerais (Brazil) as well as internal migration of students searching for higher education studies. It seeks to understand the influence of the implementation of public distance education on the dynamics of that type of migratory processes. The qualitative and quantitative methodology of the present research is based on official data from the UAB Program, focusing on undergraduate courses offered between 2012-2019 and, territorially, on hub cities offering those courses in that given period. Based on specific forms, the research also assessed the coordination, the students, and former students from UAB hub cities, in Minas Gerais. It also checked official data from the latest country demographic censuses, the PNAD-Continuous Program, and literature on internal migration in Brazil as a whole and especially in the state of Minas Gerais. In order to verify whether the Program on migrations had any influence on that particular public, it inquired about the potentiality for settlement of the population in their own municipalities and its regional integrative capacity. The results revealed that UAB has modified the territorial arrangements in interior municipalities, allowing the entry of a larger public into higher education who don’t need to displace to other municipalities or depend on daily commuting anymore. Internal migrations for education reason is a reality for all Minas Gerais mesoregions; however, migratory movements are reduced by the implementation of public distance education, which shows a trend for seasonal commuting instead. Furthermore, this study demonstrates that the teaching areas offered by UAB do not go beyond training teachers and administrators/public managers, and that might be a reason for migratory flows in many cases. Public distance education is a powerful tool to allow students living in the interior of the country access higher education without migrating; it also represents democratization of that particular type of education, thus contributing significantly to the population from Minas Gerais municipalities and their regional integration. Nonetheless, public distance education modality still needs strengthening; it requires expanding the list of courses the Program offers as well as other public policies of socioeconomic nature in order to enable the creation of jobs and acknowledgement of those individuals graduated at UAB Program.